Treatise on acoustics : the first comprehensive English translation of E.F.F. Chladni's Traité d'Acoustique /: the first comprehensive English translation of E.F.F. Chladni's Traité d'Acoustique. (2015) - Chladni, Ernst Florens Friedrich, 1756-1827
No abstract available